Labor Markets and Income Support: What Did We Learn from the Crises? - Gustavo Márquez (Inter-American Development Bank, Research Department, 2000)
The adoption of emergency employment and short-term training programs to provide income support to the population affected by the episodes of economic volatility since 1995 reveals the failure of the traditional, labor law-based income support mechanisms in the region. These emergency programs are not additional and transitory, but rather have become a permanent component of social policies. As such, they present policymakers with the opportunity to build a more encompassing and better designed mechanism to protect workers against the effects of macroeconomic volatility. The paper argues for an income support system centered on unemployment insurance, complemented with additional mechanisms to provide effective income support to workers during normal times; the paper also discusses what changes are necessary in emergency programs to make them work as part of that system.
Keywords: 330; Arbeitslosenversicherung; Arbeitslosigkeit; Arbeitsmarktpolitik; Berufsbildungspolitik; Lateinamerika